Microbiopsy Sampling for Examining Age-Related Differences in Skeletal Muscle Fiber Morphology and Composition - Hester, Garrett M.; VanDusseldorp, Trisha A.; Ha, Phuong L.; Kiani, Kaveh; Olmos, Alex A.; Jabbari, Melody; Kalladanthyil, Shania; An, SooBin; Bailly, Alyssa R.; Dalton, Benjamin E.; Bryantsev, Anton L. (Frontiers in Physiology, 2022)
Introduction: The increasingly popular microbiopsy is an appealing alternative to the more invasive Bergström biopsy given the challenges associated with harvesting skeletal muscle in older populations. Parameters of muscle fiber morphology and composition derived from the microbiopsy have not been compared between young and older adults. Purpose: The purpose of this study was to examine muscle fiber morphology and composition in young (YM) and older (OM) males using the microbiopsy sampling technique. A secondary aim was to determine if specific strength is associated with serum levels of C-terminal agrin fragment (CAF; an indicator of neuromuscular junction (NMJ) degradation). Methods: Thirty healthy, YM (n = 15, age = 20.7 ± 2.2 yrs) and OM (n = 15, age = 71.6 ± 3.9 yrs) underwent ultrasound imaging to determine whole-muscle cross-sectional area (CSA) of the vastus lateralis and rectus femoris as well as isometric and isokinetic (60°·s-1 and 180°·s-1) peak torque testing of the knee extensors. Microbiopsy samples of the vastus lateralis were collected from thirteen YM and eleven OM, and immunofluorescence was used to calculate CSA and proportion of type I and type II fibers. Results: Peak torque was lower in OM at all velocities (p ≤ 0.001; d = 1.39 - 1.86) but only lower at 180°·s-1 (p = 0.003; d = 1.23) when normalized to whole-muscle CSA. Whole-muscle CSA was smaller in OM (p = 0.001; d = 1.34), but atrophy was not present at the single fiber level (p > 0.05). Per individual, ~900 fibers were analyzed, and type I fiber CSA was larger (p = 0.05; d = 0.94) in OM which resulted in a smaller type II/I fiber CSA ratio (p = 0.015; d = 0.95). CAF levels were not sensitive to age (p = 0.159; d = 0.53) nor associated with specific strength or whole-muscle CSA in OM. Conclusions: The microbiopsy appears to be a viable alternative to the Bergström biopsy for histological analyses of skeletal muscle in older adults. NMJ integrity was not influential for age-related differences in specific strength in our healthy, non-sarcopenic older sample.